Effectiveness of Pre-procedural Mouth Rinses in Reducing Aerosol Contamination During Periodontal Prophylaxis: A Systematic Review - Mohd-Said, Shahida; Mohd-Dom, Tuti Ningseh; Suhaimi, Nawal; Rani, Haslina; McGrath, Colman (Frontiers in Medicine, 2021)
Background: Aerosol producing dental procedures has raised concerns in many for fear of spread of infection, especially during this COVID-19 pandemic. Periodontal prophylaxis is the most common aerosol producing procedure in dental practice. During COVID-19 many national and international organizations advocated the use of pre-procedural mouth rinsing for aerosol generating procedures in the dental setting; albeit many questioned the scientific basis. Objective: This review aims to evaluate existing literature on the effectiveness of pre-procedural rinsing before periodontal prophylaxis in reducing aerosol contamination in dental clinics. Methods: A comprehensive standardized literature search strategy was applied to screen and select references on attributes for reducing aerosol contamination using the PRISMA framework. Qualitative synthesis of study characteristics and findings were conducted, and Cochrane’s risk-of-bias tool for randomized trials (RoB 2) was used to assess the quality/ bias among studies. Results: The initial search yielded 731 citations found the four databases, 95 potentially effective studies were identified, with 56 effective studies. Of these 30 were randomised control trial studies and 21 had a focus on pre-procedural mouth rinsing, involving 984 participants (aged 18-70). Various pre-procedural mouthrinses were tested including most frequently chlorhexidine (CHX, 18), herbal essential oils (2), cetylpyridinium chloride (3), povidone iodine (2), chlorine dioxide (1), herbal extract (3) and other unspecified antiseptics (4). The concentrations, volume and prescribed duration of rinsing varied among studies hampering meta analyses. Nonetheless all studies identified significant reductions in bacterial contamination (as measured by colony forming units (cfu). The effectiveness of CHX over other agents was evident with more than half of the studies (7/15) reporting over a 70% reduction in bacterial contamination (cfu). There was some concerns over the risk of bias in most studies (76.2%), 19.0% at high risk of bias and 4.8% of low risk of bias. Conclusion: There is substantial evidence to support that 30sec to 20min pre-procedural mouth risings, such as with chlorohexidine can effectively reduce aerosol contamination during periodontal prophylaxis compared to rinsing with water or no rinsing.